A Systematic Literature Review of System Dynamics Application on Safety Culture - Maharani, Intan; Sudiarno, Adithya; Wirjodirdjo, Budisantoso (Fakultas Teknik UMRI, 2026)
The increasing complexity of modern industrial systems has increased the need for effective approaches to understand and improve safety performance. Safety culture is widely recognized as an important factor influencing worker behavior, accident prevention, and organizational safety outcomes, while safety programs serve as structured interventions to improve safety performance. This study aims to systematically review the application of System Dynamics (SD) in safety culture and safety program studies. A systematic literature review was conducted using the PRISMA approach which led to 22 collected articles from ScienceDirect. The review focused on publication trends, countries, industrial sectors, research designs, SD techniques, safety related variables, safety culture aspects, and the intended outcomes of SD implementation. The findings show that SD has been widely used to represent complex interactions and feedback structures in safety-related systems. However, most previous studies remain focused on model development and relationship analysis, while only a limited number have evaluated safety programs as intervention mechanisms. These findings indicate that current SD applications are still largely oriented toward understanding system complexity rather than supporting practical decision-making and intervention evaluation. Therefore, future studies should further integrate safety programs into SD-based safety culture models to support proactive intervention factor and improved safety performance.